Hubungan Kecerdasan Emosional dan Kecerdasan Spiritual terhadap Hasil Belajar TIK Siswa Kelas XI SMAN 7 Denpasar Semester Genap Tahun Ajaran 2011/2012 - Ni Luh Arie Suari (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2012)
The purpose of this research are (1) to know the degree of relationship between emotional quotient to ICT learning result at XI class students’ of SMAN 7 Denpasar; (2) to know the degree of relationship between spiritual quotient to ICT learning result at XI class students’ of SMAN 7 Denpasar;(3) to know degree of relationship between spiritual quotient and emotional quotient to ICT learning result at XI class students’ of SMAN 7 Denpasar. The method or approach used in this research was non experiment or ex post facto because the researcher did not use any treatment or manipulation the research’s variables. The researcher only gathered data according to the result of tendency that already existed naturally in the respondents. The research took place at SMAN 7 Denpasar, Jalan Kamboja No. 9, Denpasar. The subject of the research are the XI grade students. Research time was in even semester in academic year 2011/2012. The sample of this research was 233 students.  Based on to the research’s result revealed that emotional quotient and spiritual quotient factor play a role in determining the result of student learning ICT. The analyzes result showed that (1) the relationship between emotional intelligence variables (X1) with learning outcomes (Y) and spiritual intelligence (X2) still has a relationship of 0.303 is considered low, (2) the relationship between the variables of spiritual intelligence (X2) with learning outcomes (Y) with emotional intelligence (X1) still has a relationship of 0.234 categorized as low, (3) the relationship between emotional intelligence variables (X1) and spiritual intelligence variables (X2) with learning outcomes (Y) to have a relationship of 0.611 is considered strong; (4) the presences of significant relationship between   emotional quotient and the result of class XI students learning ICT at SMAN 7 Denpasar is amounting to 33,7 % and the presences of significant relationship between   spiritual quotient and the result of class XI students learning ICT at SMAN 7 Denpasar is amounting to 31%; (5) The common perception that there are significant relationship between emotional quotient and spiritual quotient to class XI students the ICT learning result at SMAN 7  Denpasar together amounting 37,3%